Integration of health services improves multiple healthcare outcomes among HIV-infected people who inject drugs in Ukraine. - Bachireddy, Chethan; Soule, Michael C; Izenberg, Jacob M; Dvoryak, Sergey; Dumchev, Konstantin; Altice, Frederick L (Drug and alcohol dependence, 2014)
People who inject drugs (PWID) experience poor outcomes and fuel HIV epidemics in middle-income countries in Eastern Europe and Central Asia. We assess integrated/co-located (ICL) healthcare for HIV-infected PWID, which despite international recommendations, is neither widely available nor empirically examined.
Keywords: Adult; Cross-Sectional Studies; Delivery of Health Care; Delivery of Health Care, Integrated; Female; HIV Infections; Humans; Male; Quality of Life; Substance Abuse, Intravenous; Treatment Outcome; Ukraine